The Brain Circuitry Underlying the Temporal Evolution of Nausea in Humans - Napadow, Vitaly (Oxford University Press, 2013)
Nausea is a universal human experience. It evolves slowly over time, and brain mechanisms underlying this evolution are not well understood. Our functional magnetic resonance imaging (fMRI) approach evaluated brain activity contributing to and arising from increasing motion sickness. Subjects rated transitions to increasing nausea, produced by visually induced vection within the fMRI environment. We evaluated parametrically increasing brain activity 1) precipitating increasing nausea and 2) following transition to stronger nausea. All subjects demonstrated visual stimulus–associated activation (P < 0.01) in primary and extrastriate visual cortices. In subjects experiencing motion sickness, increasing phasic activity preceding nausea was found in amygdala, putamen, and dorsal pons/locus ceruleus. Increasing sustained response following increased nausea was found in a broader network including insular, anterior cingulate, orbitofrontal, somatosensory and prefrontal cortices. Moreover, sustained anterior insula activation to strong nausea was correlated with midcingulate activation (r = 0.87), suggesting a closer linkage between these specific regions within the brain circuitry subserving nausea perception. Thus, while phasic activation in fear conditioning and noradrenergic brainstem regions precipitates transition to strong nausea, sustained activation following this transition occurs in a broader interoceptive, limbic, somatosensory, and cognitive network, reflecting the multiple dimensions of this aversive commonly occurring symptom.